1999
DOI: 10.1128/aem.65.3.1152-1160.1999
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Degradation of Phthalate Isomers by Methanogenic Consortia

Abstract: Three methanogenic enrichment cultures, grown onortho-phthalate, iso-phthalate, or terephthalate were obtained from digested sewage sludge or methanogenic granular sludge. Cultures grown on one of the phthalate isomers were not capable of degrading the other phthalate isomers. All three cultures had the ability to degrade benzoate. Maximum specific growth rates (μS max) and biomass yields (YXtot S) of the mixed cultures were determined by using both the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 26 publications
(26 reference statements)
1
48
1
Order By: Relevance
“…Aftring et al, showed that phthalate isomers can be degraded under anoxic conditions (Aftring et al, 1981). Although less understood than aerobic phthalate degradation, anaerobic degradation of phthalate isomers and phthalate esters was reported for numerous pure and mixed cultures under nitrate-or sulfate-reducing or methanogenic conditions (Battersby and Wilson, 1989;Kleerebezem et al, 1999;Qiu et al, 2006;Cheung et al, 2007;Liang et al, 2008), but no decisive studies on the degradation pathways have been published so far.…”
Section: Introductionmentioning
confidence: 99%
“…Aftring et al, showed that phthalate isomers can be degraded under anoxic conditions (Aftring et al, 1981). Although less understood than aerobic phthalate degradation, anaerobic degradation of phthalate isomers and phthalate esters was reported for numerous pure and mixed cultures under nitrate-or sulfate-reducing or methanogenic conditions (Battersby and Wilson, 1989;Kleerebezem et al, 1999;Qiu et al, 2006;Cheung et al, 2007;Liang et al, 2008), but no decisive studies on the degradation pathways have been published so far.…”
Section: Introductionmentioning
confidence: 99%
“…Medium, substrate and BES were added to the bottles from concentrated stock solutions. The composition of the medium has been described elsewhere [19]. Either the phthalate isomer or a mixture of the phthalate isomer and benzoate was used as substrate at concentrations between 2 and 5 mM.…”
Section: Methodsmentioning
confidence: 99%
“…Three enrichment cultures were used with the ability to degrade either phthalate, isophthalate or terephthalate. The cultures were obtained from digested sewage sludge or granular sludge and were enriched on one of the three phthalate isomers as described previously [19]. The phthalate isomer-grown cultures had the ability to degrade benzoate without a lag phase, at rates comparable to the phthalate isomers' degradation rates.…”
Section: Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that one ton of PTA production incurs 2.5-10 m 3 of wastewater that is subsequently treated before discharge into receiving water bodies, PTA production generates approximately 120-478 × 10 6 m 3 year −1 of wastewater (Kleerebezem et al, 2005;Razo-Flores et al, 2006). This wastewater contains varying concentrations of aromatic compounds (Roffia et al, 1984;Kleerebezem et al, 1999;Razo-Flores et al, 2006;Tomás et al, 2013); thus, necessitating effective treatment. Anaerobic biological processes treating PTA process wastewater (Guyot et al, 1990;Macarie, 2000;Stergar et al, 2003;Van Lier et al, 2008;Kim et al, 2012;Narihiro et al, 2015a) promote a microbial reaction where syntrophic substrate-oxidizing bacteria (syntrophs) forge a mutually supportive partnership with methanogenic archaea (methanogens) to accomplish oxidation of aromatic compounds (Qiu et al, 2006;McInerney et al, 2007;Qiu et al, 2008;Schink and Stams, 2013;Nobu et al, 2014;Aida et al, 2015;Nobu et al, 2015a, b).…”
Section: Introductionmentioning
confidence: 99%